The Emphases and Main Trends of China Studies in Thailand - Pornpawis Lhapeerakul; Yunke Zhai (Chinese Journal of International Review, 2025)
Throughout Thailand’s history, the study of the Chinese language has faced various challenges influenced by changes in the political landscape, socialist ideologies, and nationalism. These factors have impacted the development of Chinese studies in the country. However, in recent years, heightened attention to China, driven by its economic prosperity and the advancement of the Belt and Road Initiative, has emerged within Thai society. Furthermore, the strong bilateral relations between Thailand and China, their cultural connections, similar geographical contexts, and shared historical legacies — particularly in light of China’s rapid economic growth and increasing international influence — have positioned Thailand as a key participant in the Belt and Road Initiative. In response, Thailand has actively sought to enhance its friendly exchanges and cooperation with China. The Thai government has also placed greater emphasis on research related to China, with new national development plans such as “Thailand 4.0” and educational policies promoting support for Chinese studies. This paper will outline the historical context and background of Chinese studies in Thailand, discuss the facilitating role of the Belt and Road Initiative in this field, and analyze the current state of Chinese studies in Thailand, highlighting its positive developmental trends.